Single molecule studies of meso/macro porous silica materials and gradient films - Ye, Fangmao (Kansas State University, 2009)
The preparation of mesoporous/macroporous silica materials and polarity gradient thin film are introduced in this thesis. These porous silica materials and gradient materials have the potential applications as stationary phases for chemical separations, as materials for combinatorial catalysis and as absorbent/adsorbent layers for use in chemical or biological sensors. Single molecule spectroscopy is used to probe the chemical interaction between single dye molecule and porous silica matrix. Bulk fluorescence spectroscopy is used to investigate the properties of gradient film. In Chapter one, the applications of single molecule spectroscopic methods to sol-gel silica materials are reviewed, which covers a subset of the recent literature in this area and provided salient examples of the new information that can be obtained by single molecule studies. In Chapter two, both the sample preparation and experiment setup are covered. In Chapter three, the preparation of mesoporous silica film is presented. Single molecule spectroscopy is used to probe the mass transport and molecule-matrix interactions in mesoporous thin-film systems. Three different dyes of varying size, charge, and hydrophilicity are used. Silica films with/without surfactant or containing different kind surfactant are studied. The results provide new information on mass transport through the films, evidence of reversible surface adsorption, and quantitative information on variations in these phenomena with film hydration. In Chapter four, a new model describing how to explore the actual dye concentration in single molecule experiment with considering the molecule orientation is presented, which is verified to be correct by both experimental and simulated data. In Chapter five, the growth process of Methylsilsesquioxane (MSQ) particle is studied by single molecule spectroscopy, in which, the MSQ particle is treated as “native” dye molecule. In Chapter six, silica films incorporating polarity gradients are produced by using “infusion-withdrawal dip-coating” method. The gradient film is characterized by bulk fluorescence spectroscopy, water contact angle and FTIR. In Chapter seven, a brief conclusion is drawn and future directions are presented.
Keywords: single molecule spectroscopy; silica material; fluorescence correlation spectroscopy; Chemistry, Analytical (0486)